Storyworlds: clever joe - Gaines, Keith; Kavanagh, Jim (Heinemann UK, 1996)
Joe wants to see the tractor outside but can't reach the window. He cleverly empties a bin, stands on it, and gets the perfect view. The story highlights Joe$1 (Bs resourcefulness and determination to solve problems in creative ways.s